Roger Pielke Jr.'s Appallingly Bad Analysis of Billion Dollar Disasters - Blair Fix (Economics from the Top Down, 2025)
In the world of scientific disinformation, Roger Pielke Jr. is a well known player. A political scientist by training, Pielke has a long history of being a thorn in the side of climatologists who study natural disasters. [***] Pielke's latest entry in this genre is a 2024 paper called `Scientific integrity and U.S. “Billion Dollar Disasters”'. The paper takes aim at the `billion-dollar disasters' dataset run by climatologists at the NOAA. As the name suggests, the database tracks the cost of US weather and climate-related disasters which have inflation-adjusted losses that exceed 1 billion. (Or rather, the database tracked these costs. The billion-dollar-disasters database was recently cancelled by the Trump regime. Afterwards, Pielke took to his blog to celebrate.) [***] Now, my goal here is not to defend the billion-dollar-disasters dataset from Pielke's criticism. Instead, my aim is to show that Pielke's analysis is so flawed that it undermines his own appeal `scientific integrity'. For his part, Pielke claims that putting climatologists in charge of disaster loss estimation is `problematic', and that the job would be better left to `proper economists'. Furthermore, Pielke argues that the billion-dollar-disasters dataset is so faulty that it violates the NOAA's own standards on `scientific integrity'. Yet while Pielke sits on this high horse, he manages to so horribly botch his own analysis that one wonders if he is unintentionally writing satire. [***] In what follows, I'll spend a whole essay unpacking and debunking a single chart. Figure 1 shows Pielke's published analysis of the billion-dollar-disasters dataset. The graph seems to show a steady decline in average disaster costs as a share of US GDP. The implicit message is that when climatologists warn about worsening natural disasters, they're overreacting. If anything, economic growth seems to be making disaster costs more trivial. Or so Pielke claims.
Keywords: Q5; P1; 330; accounting; disaster; ecology; measurement; price; United States